Gene Therapy in Mouse Models of Deafness and Balance Dysfunction - Wang, Lingyan; Kempton, J. Beth; Brigande, John V. (Frontiers in Molecular Neuroscience, 2018)
Therapeutic strategies to restore hearing and balance in mouse models of inner ear disease aim to rescue sensory function by gene replacement, augmentation, knock down or knock out. Modalities to achieve therapeutic effects have utilized virus-mediated transfer of wild type genes and small interfering ribonucleic acids; systemic and focal administration of antisense oligonucleotides and designer small molecules; and lipid-mediated transfer of Cas 9 ribonucleoprotein complexes. This work has established that gene or drug administration to the structurally and functionally immature, early neonatal mouse inner ear prior to hearing onset is a prerequisite for the most robust therapeutic responses. These observations may have significant implications for translating mouse inner ear gene therapies to patients. The human fetus hears by gestational week 19, suggesting that a corollary window of therapeutic efficacy closes early in the second trimester of pregnancy. We hypothesize that fetal therapeutics deployed prior to hearing onset may be the most effective approach to preemptively manage genetic mutations that cause deafness and vestibular dysfunction. We assert that gene therapy studies in higher vertebrate model systems with fetal hearing onset and a comparable acoustic range and sensitivity to that of humans are an essential step to safely and effectively translate murine gene therapies to the clinic.